An estimated model for organizational performance of Small medium enterprises: proposals for future researchers In the era of the economic crisis (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This article proposes some appropriate indicators to measure the performance of Small and Medium Enterprises (SMEs) based on a situation analysis. This research type is literature study.Several expert views and research results were collected for mapping. The technical analysis of this literature study uses comparative methods, situation analysis and selecting the right indicators.The literature study results suggest a second order estimation model for organizational performance consisting of ten SMEs organizational performance indicators.Ten organizational performance indicators are divided into internal decisions measured by employee attitudes, commitment, human resources abilities, quality, service quality, efficiency and cost reduction and external decisions measured by competitive and advantage, customer satisfaction, product innovation.The results of this study are useful for researchers who want to explain organizational performance according to the perceptions of SMEs owners before conducting further research that aims to determine the contribution of SMES to the regional economy.